A new series of low-loss multicomponent oxide microwave dielectrics with a rock salt structure: Li5MgABO8 (A=Ti, Sn; B=Nb, Ta). Issue 8 (1st June 2020) - Zhang, Xing; Jiang, Zhouhang; Tang, Bin; Fang, Zixuan; Xiong, Zhe; Li, Hao; Yuan, Changlai; Zhang, Shuren
Abstract: In this study, a series of Li5 MgABO8 (A=Ti, Sn; B=Nb, Ta) compounds were designed and synthesized through a solid-state reaction method. The XRD patterns showed that a single phase was formed for all the samples. All the peaks were indexed based on the MgO-Like rock salt cubic structure with space group Fm-3m (225) and the peaks indicated that crystals presented different (111) orientation growths in the prepared samples. For all the specimens, the relative density values of 94% and above could be achieved when the sintering temperature exceeded 1300 °C. The εr values of the specimens showed an increasing trend when the sintering temperatures increased. However, the Q × f values firstly increased and then decreased with the rising temperatures. The electronically-induced strains and lattice-induced strains, which were evaluated by the bond strain index (BSI) and global instability index (GII), presented same variation trends as the Q × f values when the sintering temperature increased. The lowest dielectric loss was achieved in Li5 MgTiNbO8 ceramics: εr =17.55, Q × f=109, 700 GHz (f=7.379 GHz), τ f =-32.5 ppm/°C, when sintered at 1290 °C for 4 h.